Family Planning Practices and Associated Factors among HIV Positive Women Attending HIV Clinic of a Tertiary Care Hospital, Davangere - Arshiya Taranum; Navinkumar Angadi (Medsci Publications, 2016)
Background: Meeting contraceptive needs of HIV positive women can help to avoid unintended pregnancies which would reduce maternal deaths and paediatric HIV infections. Objectives: Objectives of this study were to determine the proportion of HIV positive women on ART using contraception and to know the factors associated with their contraception use. Methods: This is a facility based, descriptive cross-sectional study conducted from 1st October 2012 to 31st March 2013 in HIV Clinic, Bapuji Hospital, Davangere. The study subjects included were 220 HIV positive women attending HIV clinic. Statistical analysis was done using proportions and Chi-square test. Results: The proportion reporting use of contraception was 54.1%. The most common method used was condoms (54.6%), oral contraceptives (5.1%), while 33.6% had undergone tubectomy. Fear of side effects (43%) was the most common reason cited for not using contraception. Parity, Spouse HIV status, stage of disease or CD4 counts were found to be associated with contraception use. Conclusions: About half of the women on ART were not on contraception. Thus, contraceptive use among HIV-positive females was low. Counselling regarding family planning and provision of contraception services should be integrated with HIV clinic.